2018
DOI: 10.1111/cen.13738
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of high intensity focused ultrasound and radioiodine for treating toxic thyroid nodules

Abstract: In our series, RAI clearly outperforms HIFU in treating patients carrying TTN and remains the first-line noninvasive treatment in such cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Among all thermal ablation options including HIFU, RFA and laser ablation remain to be the most established and used techniques in the treatment of benign thyroid nodules [25]. In comparison, the adoption for HIFU ablation for both toxic and nontoxic thyroid diseases has been relatively slow as the longer-term efficacy remains unclear [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Among all thermal ablation options including HIFU, RFA and laser ablation remain to be the most established and used techniques in the treatment of benign thyroid nodules [25]. In comparison, the adoption for HIFU ablation for both toxic and nontoxic thyroid diseases has been relatively slow as the longer-term efficacy remains unclear [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, TA appears appropriate for patients with small AFTN who decline, or are not amenable to RAI therapy or thyroid surgery. HIFU appears as less effective than RAI since thyroid function normalization DOI: 10.1159/000506513 was obtained at 12-months in 94% of the RAI-treated versus 53% of the HIFU-treated subjects [47]. Data concerning the efficacy of MWA is presently considered insufficient.…”
Section: Hyperfunctioning Nodulesmentioning
confidence: 99%
“…High-Intensity Focused Ultrasound HIFU is less effective than RAI for control of hyperfunctioning nodules. A prospective trial in 2 cohorts treated either with HIFU or RAI demonstrated that euthyroidism at 12 months was obtained in 94% of the RAItreated versus 53% of the HIFU-treated patients [100].…”
Section: Benign Autonomously Functioning Thyroid Nodulesmentioning
confidence: 99%